1996
DOI: 10.1248/cpb.44.1454
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Saponins and Glycosides. III. Horse Chestnut. (1): The Structures, Inhibitory Effects on Ethanol Absorption, and Hypoglycemic Activity of Escins Ia, Ib, IIa, IIb, and IIIa from the Seeds of Aesculus hippocastanum L.

Abstract: Five bioactive triterpene oligoglycosides named escins, Ia, Ib, IIa, IIb, and IIIa were isolated from the seeds of horse chestnut tree, Aesculus hippocastanum L. (Hippocastanaceae). The chemical structures of escins Ia, Ib, IIa, IIb, and IIIa were determine on the basis of chemical and physicochemical evidence, which included selective cleavage of the glucuronide linkage using photochemical reaction and lead tetraacetate decarboxylation reaction. Escins Ia, Ib, IIa, and IIb were found to exhibit an ethanol abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
64
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 0 publications
4
64
0
1
Order By: Relevance
“…We previously reported that escin IIa inhibited the increase in glucose levels in glucose-loaded rats. 15,16) In the present study, the inhibitory effect of the chakasaponins tended to be stronger than that of escin IIa.…”
Section: 7)supporting
confidence: 41%
“…We previously reported that escin IIa inhibited the increase in glucose levels in glucose-loaded rats. 15,16) In the present study, the inhibitory effect of the chakasaponins tended to be stronger than that of escin IIa.…”
Section: 7)supporting
confidence: 41%
“…18) There are several reports showing that a single oral dose of a total escins fraction was found to effectively inhibit pancreatic lipase activity, 10) lower blood glucose levels and lower plasma glucose levels. 19,20) In this study, firstly we attempted to examine the effect on pancreatic lipase using 80% aqueous ethanol fractions extracted from the seeds of Aesculus turbinata BLUME. in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Escins have shown distinguished anti-inflammatory, anti-edema, capillary protective, hypoglycemic and ethanol absorption inhibitory activity. 8,9) Recently, escins have been reported to show inhibitory effects on the elevation of blood glucose levels and inhibitory effects on pancreatic lipase activity in mice. 10) Pancreatic lipase is well known to be critical lipase in the development of obesity.…”
mentioning
confidence: 99%
“…The edema was measured 1 h after dimethyl benzene treatment, and the method is the same as reported in the literature. 9,10) The ear swelling was measured by subtracting the weight of the left ear from that of the right. The inhibitory ratio (IR) was calculated as follows, where edema A: edema was induced by dimethyl benzene alone, and edema B: edema was induced by dimethyl benzene plus sample.…”
Section: )mentioning
confidence: 99%